Legal Protection for Automatic Exchange of Information Taxation in Indonesia: The Importance of Synergy with Cybersecurity Institutions - Gde Wahyu Marta Gunadi; I Nyoman Budiana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Every citizen who is the subject of taxes and already has a Taxpayer Identification Number (NPWP or NIK) must do tax reporting on his income. Such reporting ensures taxpayer property and income data validation while supporting good governance. Data automation support is needed from other agencies such as banks to find out the balance and ownership of deposits and bank securities, land bodies to know land ownership, stock exchanges to know share ownership and other institutions related to property ownership. Integration between these institutions will increase the validity of reporting property and income owned by government officials, ultimately improving integrity towards good governance. In reality, there is no automation of validation of annual notification letter (SPT) charging data on property ownership data in each institution due to the sectoral ego of each institution, and there is no real-time regulation of property validation. Automatic Exchange of Information (AEOI) enables the automated sharing of a set of information that has been previously defined by the tax authorities. AEOI is a plan of the G20 members and is initiated by the OECD. The AEOI system works through the exchange of financial data of foreign nationals living in a country. The exchange of financial data is carried out between the tax authorities in each country. Indonesia is prepared to put this into practice as a G20 member, as evidenced by the previous release of Minister of Finance Regulation Number 39/PMK.03/2017 (PMK 39), covering Procedures for Exchange of Information Based on International Agreements. Types of Documents and/or Additional Information Required to Be Retained by Taxpayers Conducting Transactions with Related Parties and Procedures for Management, Minister of Finance Regulation No. 213/PMK..03/2016 (PMK 213). As a result, in addition to the Automatic Exchange of Information (AEOI) regulation put out by the Organization for Economic Cooperation and Development, there needs to be legal protection (OECD). Furthermore, the author emphasizes the importance of cooperation and synergy with cybersecurity institutions to secure tax exchange data.